1993
DOI: 10.1128/jb.175.23.7673-7682.1993
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and molecular analyses of the C-terminal region of the recE gene from the Rac prophage of Escherichia coli K-12 reveal the recT gene

Abstract: The nucleotide sequence of the C-terminal region of the recE gene of the Rac prophage of Escherichia coli K-12 reveals the presence of a partially overlapping reading frame we call recT. Deletion mutations show that recT is required for the RecE pathway of conjugational recombination. By cloning recT with a plasmid vector compatible with pBR322, we showed by cis-trans tests that the portion of the recE gene encoding ExoVIII DNA nuclease activity is also required for RecE pathway conjugational recombination. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 36 publications
3
62
0
Order By: Relevance
“…RecT is derepressed by sbcA mutations, and some recombination events occurring in recBC sbcA recA mutant cells depend on it (Clark et al, 1993;Hall and Kolodner, 1994, and references therein).…”
Section: Dsbs Trigger Rdr In Recbc Sbca Mutant Cellsmentioning
confidence: 99%
“…RecT is derepressed by sbcA mutations, and some recombination events occurring in recBC sbcA recA mutant cells depend on it (Clark et al, 1993;Hall and Kolodner, 1994, and references therein).…”
Section: Dsbs Trigger Rdr In Recbc Sbca Mutant Cellsmentioning
confidence: 99%
“…The Red recombination functions are encoded by three adjacent genes, gam, bet and exo, in the pL operon (1). RecET functions are encoded by two adjacent genes, recE and recT, present on the cryptic lambdoid Rac prophage found in the genome of many E. coli K-12 strains (5). A variety of studies have concluded that the Exo/Beta and RecE/RecT protein pairs are functionally equivalent although not related at the sequence level (6,7).…”
mentioning
confidence: 99%
“…5). RecE and RecT form part of a minor recombination pathway encoded by a cryptic lambdoid prophage present in some strains of E. coli that is manifest in the absence of a functional RecBCD nuclease/ helicase complex (Clark et al 1993;Kolodner et al 1994). Studies of RecT suggest that despite its independent evolution, it shares with RecA some of the hallmarks of a homologous pairing protein, including the ability to unstack ssDNA bases, which may facilitate homologous contacts (Noirot et al 2003).…”
Section: Homologous Recombination By Exonucleases and Dna-annealing Pmentioning
confidence: 99%